Fluticasone propionate in clinically suspected asthma patients with negative methacholine challenge test. (10th September 2015) - Peiman, Soheil; Abtahi, Hamidreza; Akhondzadeh, Shahin; Safavi, Enayat; Moin, Mostafa; Rahimi Foroushani, Abbas
Abstract: Introduction: Despite reports of response to steroid inhaler in some clinically suspected asthma patients with negative methacholine challenge test (CSA/MCT−), treatment in these patients has not been prospectively studied. Objective: We studied the role of a 12 week high dose inhaled fluticasone trial in CSA/MCT− patients. Methods: After a 2 week run‐in period, CSA/MCT−patients were treated with 12 weeks of Fluticasone propionate 1000 µg/day. The Asthma Control Test (ACT), numeric cough score (NCS) and bronchodilator use were compared with their pretreatment values. Results: Thirty‐four of 42 CSA/MCT−patients completed the study. Mean pretreatment ACT score (pACT) was significantly increased after treatment (14.7 ± 3.37 to 20.9 ± 3.1, P < 0.001). Posttreatment values of daytime (1.0 ± 1.0) and night‐time (0.6 ± 0.9) NCS decreased compared to their pretreatment values (2.8 ± 1.1 and 1.9 ± 1.3, respectively; P < 0.001). ACT score change (ΔACT) were significantly greater in those with pACT < 15 than in those ≥15 ( P < 0.001) . Fifteen of 21 patients with ΔACT > 5 did not need to use bronchodilator for their symptom relief. Wheeze disappeared in all six patients with ΔACT > 5 after the trial. Six months after the study, steroid inhaler continued to be used by 72.2% of patients. Conclusion: A significant portion of CSA/MCT− (especially those with pretreatment ACT score <15) respond to high dose fluticasone inhaler in terms of symptoms relief, disappearance of wheeze and need to bronchodilator use. ΔACT could not be predicted with any individual symptoms or signs before MCT, % FEV1 decline or symptoms during MCT and exhaled nitric oxide.